MACC1 as a prognostic biomarker for early-stage and AFP-normal hepatocellular carcinoma. - Chan Xie (PLoS ONE, 2013)
Background The metastasis-associated in colon cancer 1 gene (MACC1) has been found to be associated with cancer development and progression. The aim of this study was to investigate the prognostic value of MACC1 in early-stage and AFP-normal hepatocellular carcinoma (HCC). Methods mRNA and protein levels of MACC1 expression in one normal liver epithelial cells THLE3 and 15 HCC cell lines were examined using reverse transcription-PCR and Western blot. MACC1 expression was also comparatively studied in 6 paired HCC lesions and the adjacent non-cancerous tissue samples. Immunohistochemistry was employed to analyze MACC1 expression in 308 clinicopathologically characterized HCC cases. Statistical analyses were applied to derive association between MACC1 expression scores and clinical staging as well as patient survival. Results Levels of MACC1 mRNA and protein were higher in HCC cell lines and HCC lesions than in normal liver epithelial cells and the paired adjacent noncancerous tissues. Significant difference in MACC1 expression was found in patients of different TNM stages (P<0.001). Overall survival analysis showed that high MACC1 expression level correlated with lower survival rate (P = 0.001). Importantly, an inverse correlation between MACC1 level and patient survival remained significant in subjects with early-stage HCC or with normal serum AFP level. Conclusions MACC1 protein may represent a promising biomarker for predicting the prognosis of HCC, including in early-stage and AFP-normal patients.